Predominant activation of MAP kinases and pro-destructive/pro-inflammatory features by TNF α in early-passage synovial fibroblasts via TNF receptor-1: failure of p38 inhibition to suppress matrix metalloproteinase-1 in rheumatoid arthritis. Issue 8 (12th January 2007) - Kunisch, Elke; Gandesiri, Muktheshwar; Fuhrmann, Reneé; Roth, Andreas; Winter, Rando; Kinne, Raimund W
Abstract : Objective: To examine the relative importance of tumour necrosis factor-receptor 1 (TNF-R1) and TNF-R2 and their signalling pathways for pro-inflammatory and pro-destructive features of early-passage synovial fibroblasts (SFB) from rheumatoid arthritis (RA) and osteoarthritis (OA). Methods: Cells were stimulated with tumour necrosis factor (TNF)α or agonistic anti-TNF-R1/TNF-R2 monoclonal antibodies. Phosphorylation of p38, ERK and JNK kinases was assessed by western blot; proliferation by bromodesoxyuridine incorporation; interleukin (IL)6, IL8, prostaglandin E2 (PGE2 ) and matrix metalloproteinase (MMP)-1 secretion by ELISA; and MMP-3 secretion by western blot. Functional assays were performed with or without inhibition of p38 (SB203580), ERK (U0126) or JNK (SP600125). Results: In RA- and OA-SFB, TNFα-induced phosphorylation of p38, ERK or JNK was exclusively mediated by TNF-R1. Reduction of proliferation and induction of IL6, IL8 and MMP-1 were solely mediated by TNF-R1, whereas PGE2 and MMP-3 secretion was mediated by both TNF-Rs. In general, inhibition of ERK or JNK did not significantly alter the TNFα influence on these effector molecules. In contrast, inhibition of p38 reversed TNFα effects on proliferation and IL6/PGE2 secretion (but not on IL8 and MMP-3 secretion). The above effects were comparable in RA- and OA-SFB, except that TNFα-induced MMP-1 secretion was reversed by p38 inhibition only in OA-SFB. Conclusion: In early-passage RA/OA-SFB, activation of MAPK cascades and pro-inflammatory/pro-destructive features by TNFα is predominantly mediated by TNF-R1 and, for proliferation and IL6/PGE2 secretion, exclusively regulated by p38. Strikingly, RA-SFB are insensitive to p38 inhibition of MMP-1 secretion. This indicates a resistance of RA-SFB to the inhibition of pro-destructive functions and suggests underlying structural/functional alterations of the p38 pathway, which may contribute to the pathogenesis or therapeutic sensitivity of RA, or both.